2005
DOI: 10.1104/pp.105.061598
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsiscyp51Mutant Shows Postembryonic Seedling Lethality Associated with Lack of Membrane Integrity

Abstract: CYP51 exists in all organisms that synthesize sterols de novo. Plant CYP51 encodes an obtusifoliol 14a-demethylase involved in the postsqualene sterol biosynthetic pathway. According to the current gene annotation, the Arabidopsis (Arabidopsis thaliana) genome contains two putative CYP51 genes, CYP51A1 and CYP51A2. Our studies revealed that CYP51A1 should be considered an expressed pseudogene. To study the functional importance of the CYP51A2 gene in plant growth and development, we isolated T-DNA knockout all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
105
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 63 publications
3
105
1
Order By: Relevance
“…The expression of Arabidopsis CYP710A genes was suggested to be under strict regulation in different tissues and organs (Figure 8), suggesting the possibility that phenotypic alterations may be observed in definite tissues at specific developmental stages. It has been reported that another P450 gene involved in sterol biosynthesis, CYP51G1, was strongly expressed in leaf vascular tissues (Kim et al, 2005), which was closely similar to the expression pattern of CYP710A1 involved in stigmasterol production (Figure 8). CYP51G1 (At1g11680) is the single functional gene (Kim et al, 2005) encoding obtusifoliol 14a-demetylase protein in Arabidopsis (Figure 1).…”
Section: Promoter:gus Fusion Analyses For Differential Expression Patmentioning
confidence: 59%
See 1 more Smart Citation
“…The expression of Arabidopsis CYP710A genes was suggested to be under strict regulation in different tissues and organs (Figure 8), suggesting the possibility that phenotypic alterations may be observed in definite tissues at specific developmental stages. It has been reported that another P450 gene involved in sterol biosynthesis, CYP51G1, was strongly expressed in leaf vascular tissues (Kim et al, 2005), which was closely similar to the expression pattern of CYP710A1 involved in stigmasterol production (Figure 8). CYP51G1 (At1g11680) is the single functional gene (Kim et al, 2005) encoding obtusifoliol 14a-demetylase protein in Arabidopsis (Figure 1).…”
Section: Promoter:gus Fusion Analyses For Differential Expression Patmentioning
confidence: 59%
“…cvp1 plants displayed postembryonic vascular patterning defects (Carland et al, 2002), and SMT2 cosuppression lines contained higher levels of campesterol and lower levels of sitosterol, exhibiting developmental abnormalities such as reduced apical dominance and reduced fertility that cannot be restored by exogenous BRs (Schaeffer et al, 2001). Furthermore, it has recently been reported that a T-DNA insertion mutagenesis within the obtusifoliol 14a-demethylase gene CYP51G1 caused defects in membrane integrity and hypocotyl elongation, leading to postembryonic seedling lethality (Kim et al, 2005). These results indicate that altered sterol profiles due to the mutations both upstream and downstream of the SMT2 step affect membrane properties, thereby influencing signaling cascades involved in normal plant growth, such as cell polarity, auxin efflux, and ethylene signaling.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing evidence indicates that plant sterols per se can act as signaling molecules. Plant sterol biosynthetic mutants, such as smt1/cph, cpi1-1, cyp51A2, fackel (fk), and hyd1, could not be rescued by BR application (Diener et al, 2000;Jang et al, 2000;Schrick et al, 2000Schrick et al, , 2002Souter et al, 2002;Willemsen et al, 2003;Kim et al, 2005;Men et al, 2008). Sterols were found to have intimate interactions with plant hormones, such as auxin and ethylene.…”
mentioning
confidence: 99%
“…As a result, the number of known CYP51 sequences exceeds 100. The reasons for the existence of homologous CYP51 genes in the same species or their precise functions remain unknown, though it was reported that only one of the two CYP51 genes from A. thaliana (CYP51A2) is functional, while the other is an expressed pseudogene [15]. Mammalian genomes contain only one CYP51 gene yet sometimes † Corresponding author: Michael R. Waterman, Tel.…”
mentioning
confidence: 99%